2017
DOI: 10.1002/2211-5463.12211
|View full text |Cite
|
Sign up to set email alerts
|

ZNT7 binds to CD40 and influences CD154‐triggered p38 MAPK activity in B lymphocytes—a possible regulatory mechanism for zinc in immune function

Abstract: Zinc deficiency impairs the immune system leading to frequent infections. Although zinc is known to play critical roles in maintaining healthy immune function, the underlying molecular targets are largely unknown. In this study, we demonstrate that zinc is important for the CD154–CD40‐mediated activation of downstream signaling pathways in human B lymphocytes. CD40 is a receptor localized on the cell surface of many immune cells, including B lymphocytes. It binds to CD154, a membrane protein expressed on antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Because T-cell concentrations did not decrease in response to zinc treatment, one can speculate that B-cell concentrations did decrease in response to PZ supplementation, but we have no way to assess that retrospectively. Two recent studies have identified 2 different zinc transporters as having key roles in B-cell biology (32,33), suggesting that further examination of this cell type is warranted. Another interpretation of this result is that zinc may have dampened a mild lymphocytosis in this population, perhaps resulting from undiagnosed infections, but this is also speculation.…”
Section: Discussionmentioning
confidence: 99%
“…Because T-cell concentrations did not decrease in response to zinc treatment, one can speculate that B-cell concentrations did decrease in response to PZ supplementation, but we have no way to assess that retrospectively. Two recent studies have identified 2 different zinc transporters as having key roles in B-cell biology (32,33), suggesting that further examination of this cell type is warranted. Another interpretation of this result is that zinc may have dampened a mild lymphocytosis in this population, perhaps resulting from undiagnosed infections, but this is also speculation.…”
Section: Discussionmentioning
confidence: 99%
“…CD40 is linked to zinc transporter ZnT7 expression in the regulation of immune function of human B lymphocytes. Knockdown of ZnT7 in B lymphocytes decreases expression of CD40 on the cell surface [ 73 ]. Conversely, the A/A genotype, rs430759, of the zinc transporter ZnT6 is associated with a low susceptibility to RA severity, suggesting a protective role of this particular genotype [ 74 ].…”
Section: Zinc and Cadmium In The Aetiology And As Risk Factors Of mentioning
confidence: 99%
“…These antibodies recognize and bind to antigens specifically, thereby activating several immune responses (3) that selectively eliminate microorganisms, viruses, and other foreign molecules (31). Zinc deficiency impairs B lymphocyte development and the production of antibodies, especially IgG (32). ZM supplementation reportedly enhanced the resistance to infection by increasing the total immunoglobulin concentration in weaning calves (29).…”
Section: Discussionmentioning
confidence: 99%